(untitled) (Research, Society and Development, 2024)
Nutrigenomics is a multidisciplinary area of science that studies the interaction of diet and nutrients, along with an Obesity is a disease characterized by fat gain, in na amount that afeccts the health of individuals, resulting in chages in metabolismo and respiratory problems. Our country is in 5th place in the world ranking, with apprroximately 60 milion overweight anda 22 million obese. The objective of study was evaluate binge eating disorder present among obese patients in the pre-and post-bariatric periods. Resarch was carried out on articles, books, and health pre-and post-bariatric patients. Between the Years 2010 to 2023, at research sites BIREME and SCIELO.The DeSC descriptors for the search corresponded to: eating disorder in obese patients, bariatric surgery, obesity, binge eating, anxiety. In the research results, it was possible to notice that the highest incidence of binge eating before and after bariatric surgery was among women and in the average age group of 40 years. Multidisciplinary monitoring both before and after surgery is extremely important. We emphasize that pre-operatively there is a need for weight loss to meet the requirements for surgery. Reinforcing that long post-operative follow-up is also extremely important, as there is a significant percentage of weight regain up to two years after surgery. In the current scenario, we have the enormous importance of trying to combat obesity cases in the world.